Foundations of mixed methods research integrating quantitative and qualitative approaches in the social and behavioral sciences - Tashakkori, Abbas; Johnson, Burke; Teddlie, Charles
"The highly-anticipated second edition of the Foundations of Mixed Methods Research:Integrating Quantitative and Qualitative Approaches in the Social and Behavioral Sciences gives students a comprehensive overview of mixed methods from philosophical roots and traditions through designing, conducting, and disseminating a study. Authors Abbas Tashakkori, Burke Johnson, and Charles Teddlie have thoroughly updated the text to reflect the many advances over the last decade in mixed methods. New example studies throughout and a new appendix highlight the latest research on mixed methods and current best practices. New sections on evaluating quality in mixed methods studies and writing up research results round out the process of mixed methods research. The authors have added features like content summaries and objectives at the beginning of each chapter and chapter summaries and previews at the end of each chapter aid readers in their mixed methods journey"--Provided by publisher.